Faktor-Faktor Yang Berhubungan Dengan Status Gizi Pada Balita Di Puskesmas Muara Nasal Kabupaten Kaur Tahun 2022 - Anderson, Jemi; Maryasari, Fikitri; Retni, Retni (Journal Hygeia Public Health, 2022)
WHO in 2018 estimates that there are 161 million toddlers experiencing nutritional problems. The biggest nutritional problem occurs in toddlers reaching 51 million toddlers. Under-5 mortality due to nutrition is 2.8 million people and 2 suffer from micronutrient deficienciesbillion. The problem of malnutrition and malnutrition is still a major problemin Indonesia. In Indonesia, the problem of malnutrition causes four ofa hundred babies born each year cannot survive more thanfive years, which is generally a victim of illness and condition which is exacerbated by the nutrition problem; one in three children under five experienced growth disturbances and almost a fifth of the number of children under five experience less weight. (Kemenkes RI. 2018). In Kaur district, in 2022 there will be 967 toddlers with malnutrition under five status. Of the 967 toddlers whose nutritional status was lacking, the most at the Muara Nasal Health Center were 242 toddlers with less nutritional status than the number of toddlers in the working area of ​​the Muara Nasal Health Center as many as 5,711 toddlers.This study used a quantitative method with a cross-sectional research design. The population in this study were all toddlers who were and were recorded at the Muara Nasal Health Center Register in Kaur Regency in 2022 as many as 5711 people. the sample in this study were 98 people.The results of this study indicate that there is a relationship between the level of knowledge and the nutritional status of toddlers in the working area of ​​the Muara Nasal Health Center, Kaur District. there is a relationship between maternal age and the nutritional status of toddlers in the working area of ​​the Muara Nasal Health Center, Kaur Regency, and there is a relationship between exclusive breastfeeding and the nutritional status of toddlers in the working area of ​​the Muara Nasal Health Center, Kaur Regency Suggestion The results of this study can be used as material for consideration for the Muara Nasal Public Health Center to improve the handling of nutritional status in caring for their children through increasing the participation of husbands in supporting their wives in caring for their children, both supporting personnel, moral and material in caring for toddlers with nutritional status. and for parents of toddlers it is hoped that the puskesmas can conduct counseling, especially about the many diseases that are caused, especially the nutritional status of toddlers.